The mathematics connection ability of 8th grade students’ in terms of cultural capital in brain-based learning - Nugraheni, Maulina Dhyan; Junaedi, Iwan (Unnes Journal of Mathematics Education, 2019)
The main objective of this study was to determine the pattern of students’ mathematics connection ability as a result of the application of Brain-Based Learning on experimental class and conventional learning on control class in grade 8 SMP Negeri 32 Semarang. This research using mix method concurrent embedded design with quantitative as the primary method. The results of this study indicate that: (1) Brain-Based Learning is effective in students’ mathematics connection ability grade 8; and (2) the description of students’ mathematics connection ability grade 8 in terms of cultural capital in mathematics learning with Brain-Based Learning.